The Importance Of Piercings In The Cultures Of The World - Agnieszka Nieradko; Andrzej Borzęcki (Kazimierz Wielki University, 2017)
The Piercing is, next to a tattoo, one of the most prevalent forms of modification of our body. If we wanted to trace human history, it could be noted that the people from the dawn of time and they would leave permanent marks on your body. They were both tattoos and different types of piercing, which today we call with piercing.